PERAN KEMAMPUAN MANAJERIAL SEBAGAI MEKANISME PENINGKATAN KUALITAS LABA DAN NILAI PERUSAHAAN - Ng, Suwandi; Daromes, Fransiskus E. (Jurnal Akuntansi dan Keuangan Indonesia, 2016)
This research is aimed to investigate the role of managerial ability as a mechanism to improve earnings quality as a mediating effect influence on firm value. The sample used in this study were non-financial companies listed on the Indonesia Stock Exchange from 2010 to 2014. The sample were selected using purposive random sampling method. The number of sample resulted form this method are 178 companies. By using path analysis method, the results show that managerial ability has positive and significant relationship to the earnings quality and firm value. In addition, Sobel's test results show that earnings quality does not mediate the effect of managerial ability on firm value.